2015
DOI: 10.5792/ksrr.2015.27.4.240
|View full text |Cite
|
Sign up to set email alerts
|

Is Single-Radius Design Better for Quadriceps Recovery in Total Knee Arthroplasty?

Abstract: PurposeAlthough single-radius (SR) designs have a theoretical advantage in quadriceps recovery following total knee arthroplasty (TKA), there has been a paucity of objective evaluation studies.Materials and MethodsOne hundred and twenty minimally invasive TKAs were prospectively randomized by a single surgeon into 2 groups: SR design TKA group and multi-radius design TKA group. Quadriceps force and power were assessed using a dynamometer, and clinical data were investigated preoperatively and 6 weeks, 3 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
0
20
1
Order By: Relevance
“…We identified 595 articles initially through both online and manual searches undertaken up to February 2020. After we applied the exclusion criteria, ultimately nine RCTs remained to be analyzed in this meta-analysis [14,[19][20][21][22][23][24][25][26] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 595 articles initially through both online and manual searches undertaken up to February 2020. After we applied the exclusion criteria, ultimately nine RCTs remained to be analyzed in this meta-analysis [14,[19][20][21][22][23][24][25][26] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [12] reported that a prolonged duration was required in patients undergoing the MR design to perform the sit-to-stand test than those undergoing the SR design as assessed by 3-dimensional kinematics. Larsen et al [17] and Kim et al [19] reported higher extensor strength in SR knees than that in their MR counterparts. Although SR protheses showed better results in [21] conducted an isokinetic study and observed better extensor performance with decreased flexion peak torque and increased extension peak torque in patients with SR design than those with MR design.…”
Section: Discussionmentioning
confidence: 94%
“…Clinical studies that compared the SR and MR femoral design yielded contradictory results [14][15][16][17][18][19]. Liu et al conducted a meta-analysis in order to find the difference in clinical outcomes between the SR and MR femoral design.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, knee prosthetics with multi-radius design over the femoral component have been used; however, recent development of single-radius knee implants have shown improvements in both mechanical and clinical functions of the knee after TKA [8,13,14,18,[26][27][28][29][30]. In these implants, the biomechanical functions are improved by lengthening the extensor moment arm, providing longer distal and posterior axis, and by maintaining the isometry of the rotation and force distribution throughout the range of motion resulting in less patellar load [7,8,31,32].…”
Section: Discussionmentioning
confidence: 99%